Students perspectives on popular narratives of romantic relationships from the perspective of moral values - Roichanah Roichanah; Yuniar Mujiwati; Innayatul Laili (Journal of Law Science, 2026)
In the digital era, popular narratives on social media have significantly shaped Generation Z’s views on romantic relationships, often promoting temporary interactions such as situationship, toxic relationship, talking stage, and marriage is scary, which potentially conflict with traditional moral values. This study aims to explore students’ perspectives on popular narratives of romantic relationships from the perspective of moral values at PGRI Wiranegara University. Employing a qualitative descriptive approach, data were collected through in-depth interviews, observation, and documentation from purposively selected Generation Z students who had romantic relationship experience and exposure to digital narratives. Data were analyzed using the Miles and Huberman interactive model with source, methodological, and temporal triangulation to ensure validity. The results show that students are familiar with various popular narratives spread through TikTok and Instagram, yet they do not accept them passively. Moral values especially responsibility, honesty, loyalty, and mutual respect serve as the main filter in evaluating these narratives, strengthened by family, religion, personal experience, peers, and campus character education. In conclusion, students actively use their moral values to critically assess popular narratives, highlighting the importance of strengthening digital literacy and moral education so that Generation Z can navigate digital culture responsibly.